Implementation of Strengthening Character Education at UPT SMK Negeri Campalagian Polewali Mandar - Jamaluddin Jamaluddin; Mila Angraeni; Risma Niswaty; Suprianto Suprianto (Jurnal Office, 2022)
The implementation of the Strengthening Character Education program cannot be separated from the role of all parties in the school. This research is a descriptive research using a qualitative approach. With as many as seven subjects, namely the Deputy Head of Curriculum, Deputy Head of Student Affairs, 2 teachers, and 3 students of the Campalagian State Vocational School. Data collection techniques using observation methods, interview methods, and documentation methods. Data analysis techniques in this study used data reduction techniques, data presentation, conclusions and verification. The results showed that the Implementation of Strengthening Character Education at UPT SMK Negeri Campalagian, seen from the results of data analysis, was included in the effective category. This can be seen from the fulfillment of the three indicators, namely the cultivation of strengthening integrated character education in subjects, the existence of extracurricular activities with the aim of forming the character of students, and habituation activities through school culture. In this study, the Campalagian State Vocational School teachers need to be creative in arranging learning and activities at school while still considering character education during the Covid-19 period. Character education during the pandemic will provide a pattern of living with character anywhere and under any conditions.